Atg5 Regulates Selective Autophagy of the Parental Macronucleus during Tetrahymena Sexual Reproduction - Tao Bo (MDPI AG, 2021)
Nuclear autophagy is an important selective autophagy process. The selective autophagy of sexual development micronuclei (MICs) and the programmed nuclear degradation of parental macronucleus (paMAC) occur during sexual reproduction in Tetrahymena thermophila. The molecular regulatory mechanism of nuclear selective autophagy is unclear. In this study, the autophagy-related protein Atg5 was identified from T. thermophila. Atg5 was localized in the cytoplasm in the early sexual-development stage and was localized in the paMAC in the late sexual-development stage. During this stage, the degradation of meiotic products of MIC was delayed in atg5i mutants. Furthermore, paMAC was abnormally enlarged and delayed or failed to degrade. The expression level and lipidation of Atg8.2 significantly decreased in the mutants. All these results indicated that Atg5 was involved in the regulation of the selective autophagy of paMAC by regulating Atg8.2 in Tetrahymena.